Early intravenous immunoglobulin use improves live birth outcomes in women with recurrent pregnancy loss: a propensity score–matched cohort study - Xin, Wenhu; Mu, Fangxiang; Wang, Kexin; Wang, Fang (Frontiers in Immunology, 2026)
ObjectiveThis study aimed to evaluate the association between intravenous immunoglobulin (IVIG) treatment and pregnancy outcomes among women with recurrent pregnancy loss (RPL) in China.MethodsWe conducted a retrospective cohort study involving RPL pregnant women who delivered at the Lanzhou University Second Hospital between April 2023 and August 2024. Participants were categorized into a treatment group (received IVIG during pregnancy) and a control group (not received). The pregnancy outcomes were live birth rate (LBR), preterm birth, birth weight, and neonatal unit admission. RPL pregnant women exposed to IVIG were matched to unexposed in a 1:1 ratio with propensity score matching (PSM), using the nearest neighbor matching. Multivariable logistics regression was used to assess the association between IVIG use during pregnancy and pregnancy outcomes. We further conducted a stratified analysis based on the mean daily dose and the gestational age at the initiation of IVIG administration.ResultsA total of 504 RPL pregnant women were included, of whom 173 received IVIG during pregnancy and 331 did not. After PSM, 276 patients were analyzed with balanced baseline characteristics. The primary analysis showed that IVIG treatment during pregnancy was associated with a significantly higher LBR compared to controls (60.1% vs. 44.9%; adjusted OR [aOR]=1.960). This association remained significant after excluding cases with embryonic abnormal karyotypes (64.3% vs. 46.3%; aOR=2.187). Stratified analyses indicated that a mean daily IVIG dose <20 g was associated with improved LBR (aOR=2.484), and the benefit persisted after excluding abnormal karyotypes (aOR=3.000). Additionally, initiation of IVIG between 6–12 weeks’ gestation yielded higher LBR (72.8% vs. 44.9%; aOR=3.253), especially among participants without abnormal karyotypes (76.6% vs. 46.3%; aOR=3.757). No significant associations were observed between IVIG use and preterm birth rate, birth weight, or neonatal unit admission rate.ConclusionsIVIG use during pregnancy was associated with a significantly higher LBR among RPL women, particularly when initiated between 6–12 weeks of gestation and administered at a dose <20 g/d; these associations remained robust after excluding cases with abnormal karyotypes. These findings suggest that IVIG may be an effective immunological intervention for improving pregnancy outcomes in selected RPL patients.